1970
DOI: 10.2172/4134486
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of C Type Virus Particles From Leukemic and Lymphocytotic Cattle.

Abstract: Thts repor t waa propn red as an acco unt of Give rome nt spon sored work . Nelth er the Unite d A. Make s any warra nty or repre senta llon, expre ssed or I mpli ed, wilh respe ct to the accu -/,cy, comp leten ess, or u//fu lnies of the infor matio n conta ined M this repo rt, or thal the use of any Worm alon. appa ratus , meth od, or proc ess diRc losed in Ws repo rt may not infrin ge priva tely own ed right a: or ' B. Assu mes any liabil lies /th resp ect to the use of, or for dima ge8 resu lUng from the I … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

1972
1972
1987
1987

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…A definite association between bovine leukaemia virus (BLV) and lymphosarcomatous lesions of cattle was first reported by Miller et al (17) and later confirmed by other workers (7,29,30). Subsequently Miller et al (19) and several other workers established that BLV is leukaemogenic and can cause lymphosarcoma in experiment ally inoculated cattle.…”
Section: Introductionmentioning
confidence: 71%
“…A definite association between bovine leukaemia virus (BLV) and lymphosarcomatous lesions of cattle was first reported by Miller et al (17) and later confirmed by other workers (7,29,30). Subsequently Miller et al (19) and several other workers established that BLV is leukaemogenic and can cause lymphosarcoma in experiment ally inoculated cattle.…”
Section: Introductionmentioning
confidence: 71%
“…It is spherical in shape with a diameter of 60-125 nm (Calafat et al . , 1974; Calafat and Ressang, 1977aRessang, , 1977bDutta et al . , 1970;Miller et al .…”
Section: Bovine Leukemia Virusmentioning
confidence: 99%
“…Electron microscopic studies have demonstrated C-type particles in the lymphocyte cultures of cattle with leukemia (3,4,13,23).…”
Section: Introductionmentioning
confidence: 99%